On the chaotic behavior of the non‐ideal vibrating systems. Issue 1 (21st October 2015) - Chiroiu, Veturia; Dumitriu, Dan
Abstract: The paper discusses the chaotic behavior of a vibrating structure coupled to an energy source. The structural response of this system may act like energy sink under certain conditions so that a part of the energy supplied by the source is spend to vibrate the structure rather than increasing the drive speed, according to the Sommerfeld effect [1]. The energy source is influenced by the response of the system and consequently, the system exhibits jumps at critical values of the energy source. The system mimics a disappearance of the energy in the resonance regions which can affect the stability of the system, sending it to chaos [2‐4]. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)